Inhibition of RIPK1 kinase does not affect diabetes development: β-Cells survive RIPK1 activation - Tatiana Takiishi; Peng Xiao; Marie Franchimont; Eduardo H. Gilglioni; Erick N. Arroba; Esteban N. Gurzov; Mathieu JM. Bertrand; Alessandra K. Cardozo (Elsevier, 2023)
Objectives: Type 1 diabetes (T1D) is caused by progressive immune-mediated loss of insulin-producing β-cells. Inflammation is detrimental to β-cell function and survival, moreover, both apoptosis and necrosis have been implicated as mechanisms of β-cell loss in T1D. The receptor interacting serine/threonine protein kinase 1 (RIPK1) promotes inflammation by serving as a scaffold for NF-κB and MAPK activation, or by acting as a kinase that triggers apoptosis or necroptosis. It is unclear whether RIPK1 kinase activity is involved in T1D pathology. In the present study, we investigated if absence of RIPK1 activation would affect the susceptibility to immune-mediated diabetes or diet induced obesity (DIO). Methods: The RIPK1 knockin mouse line carrying a mutation mimicking serine 25 phosphorylation (Ripk1S25D/S25D), which abrogates RIPK1 kinase activity, was utilized to assess the in vivo role of RIPK1 in immune-mediated diabetes or diet induced obesity (DIO). In vitro, β-cell death and RIPK1 kinase activity was analysed in conditions known to induce RIPK1-dependent apoptosis/necroptosis. Results: We demonstrate that Ripk1S25D/S25D mice presented normal glucose metabolism and β-cell function. Furthermore, immune-mediated diabetes and DIO were not different between Ripk1S25D/S25D and Ripk1+/+ mice. Despite strong activation of RIPK1 kinase and other necroptosis effectors (RIPK3 and MLKL) by TNF+BV6+zVAD, no cell death was observed in mouse islets nor human β-cells. Conclusion: Our results contrast recent literature showing that most cell types undergo necroptosis following RIPK1 kinase activation. This peculiarity may reflect an adaptation to the inability of β-cells to proliferate and self-renewal.